Azacitidine fails to eradicate leukemic stem/progenitor cell populations in patients with acute myeloid leukemia and myelodysplasia - Craddock, C; Freeman, S; Siddique, S; Raghavan, M; McSkeane, T; Arrazi, J; Brookes, C; Quek, L; Goardon, N; Aztberger, A; Vyas, P; Schuh, A; et al. (2013)
Epigenetic therapies demonstrate significant clinical activity in acute myeloid leukemia (AML) and myelodysplasia (MDS) and constitute an important new class of therapeutic agents. However hematological responses are not durable and disease relapse appears inevitable. Experimentally, leukemic stem/progenitor cells (LSC) propagate disease in animal models of AML and it has been postulated that their relative chemo-resistance contributes to disease relapse. We serially measured LSC numbers in patients with high-risk AML and MDS treated with 5'-azacitidine and sodium valproate (VAL-AZA). Fifteen out of seventy-nine patients achieved a complete remission (CR) or complete remission with incomplete blood count recovery (CRi) with VAL-AZA therapy. There was no significant reduction in the size of the LSC-containing population in non-responders. While the LSC-containing population was substantially reduced in all patients achieving a CR/CRi it was never eradicated and expansion of this population antedated morphological relapse. Similar studies were performed in seven patients with newly diagnosed AML treated with induction chemotherapy. Eradication of the LSC-containing population was observed in three patients all of whom achieved a durable CR in contrast to patients with resistant disease where LSC persistence was observed. LSC quantitation provides a novel biomarker of disease response and relapse in patients with AML treated with epigenetic therapies. New drugs that target this cellular population in vivo are required. © 2013 Macmillan Publishers Limited All rights reserved.